(untitled) (Cardiovascular Journal, 2013)
Background: Metabolic syndrome (MS) results from clustering of cardiovascular risk factors occurring in association with insulin resistance and obesity. With the increasing prevalence of obesity worldwide, MS is of keen interest in research. The disorder is defined in various ways, but one consolidated definition is needed to make studies comparable worldwide. The study was to determine the risk factors of metabolic syndrome in Bangladesh and comparison of newly proposed definition of International Diabetes Federation (IDF), modified National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) and the World Health Organization (WHO) criteria and their agreements. Materials and Methods: This was a cross sectional hospital based study. We randomly selected 229 participants. After obtaining informed written consent data collectors collected data by interview, clinical examination, anthropometric measurement and investigations. We calculated independent sample t-test means between to distinguish which risk factors were present in participants with and without MS, using SPSS v17. Results: The percentage of risk factors of MS among subjects according to different criteria was 72% of Modified ATP-III, 69% of IDF and 39% of WHO definition .In Modified NCEP ATP III when did independent sample t-test mean of BMI, waist circumference, systolic blood pressure, diastolic blood pressure, fasting blood glucose, high density lipoprotein and triglyceride were present statistically significant difference between without MS and with MS (p<0.05). According to WHO criteria BMI, waist circumference, fasting blood glucose were statistically significant (p<0.05) and similarly fasting blood glucose & triglyceride were statistically significant difference between without MS and with MS (p<0.05) according to IDF criteria.ATP III and WHO criteria showed good agreement (k 0.56) compared to ATP III with IDF (k 0.31) and WHO with IDF (k 0.11) criteria. Conclusion: Metabolic syndrome is highly prevalent in Bangladesh. We detected the highest proportion of participants with MS using the ATP III definition, which emphasizes the predominant focus on the modified waist circumference for Asian participants. However, MS prevalence following WHO criteria in those with impaired glucose regulation is comparable with ATP III definition. Follow up study needed to examine the significance of MS following all definitions for the assessment of risk for diabetes and or cardiovascular disease. Cardiovascular Journal Volume 6, No. 1, 2013, Page 17-22 DOI: http://dx.doi.org/10.3329/cardio.v6i1.16110